Studies on the Formation and Processing of Aluminium Dross with Particular Focus on Special Metals - Stefan Wibner; Helmut Antrekowitsch; Thomas C. Meisel (Metals, 2021)
In terms of production volume, aluminium is the leading metal in non-ferrous metallurgy. In particular, the recycling of aluminium-containing residues has strongly increased in recent years and will continue to gain importance in the future. Due to the high affinity of aluminium to oxygen, the oxidation of the molten bath is unavoidable, which leads to the formation of dross on the surface. This has a high content of metallic aluminium and therefore represents a valuable residual material that must be further processed. In the presented work, a study is conducted on the formation and possible further processing of aluminium dross. Within the scope of this experimental work, the pyrometallurgical treatment of Al-dross in the salt drum furnace was evaluated on the basis of an experiment in a TBRC (top blown rotary converter) by adding a salt mixture. In addition, the behaviour of special metals, in particular the rare earth elements (REEs), was investigated during such a melting process. This knowledge will be particularly important in the future, as inadequate scrap processing leads to more of these partially valuable contaminants entering the aluminium scrap cycle. The result of the experimental study was that the metal yield of the dross used in the melting experiment at the Chair of Nonferrous Metallurgy was higher than that achieved by external reprocessing. Regarding the distribution of the rare earths, there was a direct transition of these from the dross into the emerging salt slag phase.